Subsídios para uma avaliação da política pública de defesa da criança e do adolescente do conselho tutelar do município de Horizonte/Ceará: uma proposta metodológica do retrato experiencial - Santos, Antonio Nacilio Sousa dos (2022)
The objective of a policy evaluation involves actors, contexts, languages, perspectives and, mainly, the use of a methodological tool that is capable of analyzing all their biases, in their specific manifestations. It is justified that the main literature directed, first, to shed light on evaluation rests on conceptual assumptions that obscure important particularities for evaluating a policy. In some moments, the diversity and complexity in which the context and the actors of politics allow us to glimpse and go through other paths is reduced. In view of this, we are faced with the demand for other means and methodological paths that deal with elements that have been used until then, but not with the necessary vigor and intensity that can tell us about the complexity of the policy to be evaluated. Therefore, in a fruitful dialogue with the experiential evaluation of Raul Lejano (2012), combined with the methodology of the sociological portrait of Bernard Lahire (2004), in this dissertation, we develop and show the cognitive gains of an evaluative policy proposal that is central to the particularities of the social agent of politics. With this, we propose an evaluation methodology that we call experiential portrait, guided by the originality of combined elements, radically relational and directed from the demands that actors and contexts need to consider for an evaluation of a policy. That said, the research followed two paths: a) the theoretical-methodological construction of a proposal for the evaluation of public policies, centered on the creation of the experiential portrait of the social agent that develops the policy and, b) on the application of the methodological proposal of evaluation from (1) an experiential portrait of a social agent, to specifically present subsidies for an evaluation of the public policy for the defense of children and adolescents of the Tutelary Council (CT) of the municipality of Horizonte, State of Ceará. To this end, we made use of a strong immersion of analytical elements, centered on Lahire's (2004) concepts of disposition, conjugated from nexuses of approximate meanings to Lejano's (2012) concept of context. Thus, our view was guided towards an evaluation that considers essential the provisions that were created from the experiments of social agents in their life trajectory, as well as the context of the development of that policy. As a result, the dissertation work states that the content of the experiential portrait of the social agent makes it possible to evaluate a public policy based on its provisions, as they emerge, even with different intensities, in the actions of the application of the public policy for the defense of children and adolescents. . With this, it is concluded that the evaluative methodological proposal of the experiential portrait comes to constitute another tool to clarify the consensus and dissent in the development of a public policy, to constitute its evaluation.